Pengaruh Kualitas Pelayanan Perbankan Syariah Terhadap Kepuasaan Nasabah - Mukaffi, Zaim Mukaffi; Pratomo, Ahmad Sidi; Choiruddin, Muhammad Nanang (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2016)
The research aims to; analyze whether the variable partial effect of service quality on customer satisfaction on Islamic Banking in Malang, determine and analyze whether the variable service quality simultaneously influence on customer satisfaction on Islamic Banking in Malang, knowing which variables among the service variable most dominant influence on on customer satisfaction on Islamic Banking in Malang. Analysis of the data in this study using multiple linear regression test subsequently used the F test, T and dominant to see the effect of each.The research result indicate that the value of F-test (3.722) F table (2.437) this indicates that variable tangibles, reliability, responsiveness, assurance, and empathy simultaneously (together) effect on customer satisfaction. While the partial test for tangibles variable (X1) where t test (1232) t table (2,571) this indicates that tangibles no effect on customer sataisfaction. For reliability (X2), t test (3428) t table (2571), that effect the reliability of customer satisfaction. For variable responsiveness (X3), t test (-.390) t table (2,571) responsiveness no effect on customer satisfaction. To guarantee (X4), t test (0.549) t table (2,571), variable warranty does not effect the customer satisfaction. For variable empathy (X5) regression coefficient of -0103, the t test (-0667) t table (2,571) and a variable empathy has no effect on customer satisfaction. While the dominant variable in yhe quality of services that effect customer satisfaction in the city of Malang Islamic Banking is variable Assurance (X$) with a contribution of 51%.